Nanyang Cafe : a business plan - Boey, Chwee Kiang (2008)
The aim of our applied research report (ARP) is to find out the feasibility of setting up café in Nanyang Technological University (NTU). A field study was conducted among the students and staff in NTU, and then a series of analysis was made to evaluate comprehensively the feasibility of setting the café.